Intracellular andin Vitro-Translated 27-kDa Proteins Contain the 3C-like Proteinase Activity of the Coronavirus MHV-A59 - Lu, Xiaotao (Virology, 1996)
The coronavirus mouse hepatitis virus-A59 (MHV-A59) encodes a serine-like proteinase (3C-like proteinase or 3CLpro) in ORF 1a of gene 1 between nucleotides 10209 and 11114. We previously have demonstrated that proteins expressedin vitrofrom a cDNA clone of the 3CLpro region possess proteinase activity, and that the proteinase is able to cleave substratein trans.We sought to determine if the 27-kDain vitrocleavage product (p27) was an active form of the 3CLpro and whether this was consistent with the 3CLpro expressed in virus-infected cells. Antibodies directed against the 3CLpro domain detected 27-kDa MHV proteinsin vitroand in MHV-A59-infected cells. The 27-kDa proteins were able to cleave substratein transwithout other protein cofactors or supplemental membranes, and the p27 proteinase activity was retained after purification by immunoprecipitation and gel electrophoresis. When p27 was expressedin vitrowith portions of the amino- and carboxy-terminal flanking domains (MP1 and MP2), p27 was not liberated byciscleavage. The proteolytic activity of the 27-kDa proteins was inhibited by a variety of cysteine and serine proteinase inhibitors, and was eliminated by the cysteine proteinase inhibitor E64d. These results indicate that the 27-kDa protein is a mature proteinase in MHV-A59-infected cells, and that appropriate processing of this molecule occursin vitro.